Insights on the apparel needs and limitations for athletes with disabilities: the design of wheelchair rugby sports-wear - Bragança, Sara (2018)
Wheelchair rugby is a sport that has been gaining popularity with athletes with disabilities. However, as it is relatively new and not played by the masses, market specific sports-wear is not available for this sport, which impacts directly on performance and clothing satisfaction of the athletes. Therefore, the main objective of this research was to identify the problems that wheelchair rugby players face with the sports-wear they use for playing the game. The data was collected using a focus group and a questionnaire with 61 wheelchair rugby players in the United Kingdom. Based on their suggestions, on the team expertise, and on the literature, a set of design recommendations was proposed for the upper body garments (tops), lower body garments (bottoms), and gloves. The results demonstrated that the gloves currently available negatively impact on players' ability to participate with satisfactory levels of protection and comfort. Moreover, tops and bottoms also present issues, mainly in the fit and ability to regulate the core body temperature. Hence, the recommendations proposed can provide designers with key information on the specific sports-wear requirements and allow them to design and develop products that can satisfy real needs of specific end-users. This paper intends to raise awareness of the needs of sports-wear for those playing wheelchair rugby and promote the inclusivity of athletes with disabilities.